Design of a biomimetic cellulose nanofibre-based double information encryption sensor for fingerprint imaging. (15th February 2023) - Quan, Zongyan; Xue, Fei; Li, Haoyuan; Chen, Zhiping; Zhu, Hongxiang; He, Hui
Abstract: The development of double encryption system enables information to switch reversibly between "False" and "True", which helps to ensure information security in the transmission process. Herein, a biomimetic cellulose nanofibre-based double information encryption sensor (CNF-DIES) with an excellent pH response and fluorescence colour-switching performance was prepared with fluorescein isothiocyanate and protoporphyrin IX modified acetylated cellulose nanofibres (ACNF) as the pH response switch and background, respectively. Interestingly, with the addition of cellulose, CNF-DIES can be regarded as both a dye and an ink binder, which can realize direct writing function. The fluorescein grafted to ACNF guaranteed the stability of writing and avoided the "coffee ring" phenomenon. The handwriting written by CNF-DIES processes excellent light/pH double encryption performance. Besides, the film prepared by CNF-DIES can realize high resolution fingerprint imaging. This work demonstrated a strategy for pH-responsive colour-tunable materials for sensors and double information encryption. Graphical abstract: Unlabelled Image